PENGARUH PUPUK SERBUK CANGKANG TELUR DAN KONSENTRASI ZPT ROOT¬-UP TERHADAP PERTUMBUHAN SETEK BATANG BUAH NAGA SUPER MERAH (Hylocereus costaricensis) - Mohamad Fadli; Candra Catur Nugroho; Pasrul Aswat (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2019)
This study aims to determine the effect of eggshell powder fertilizer and the concentration of ZPT Root-up on the growth of super red dragon fruit stem cuttings (Hylocereus costaricensis). This research was conducted from October to December 2018 starting from the preparation of planting media to the end of the study. The research location is located in Sukodono Hamlet, Sumber Sari Village, Loa Kulu Subdistrict, Kutai Kartanegara Regency.This study was arranged in a Randomized Block Design (RBD) with a 3x4 factorial analysis with replications 3 times. The first treatment factor was the administration of ZPT Root-up (P) which consisted of three levels, namely: p0 = no treatment, p1 = 100 ppm Root-up, p2 = 200 ppm Root-up. The second treatment factor is the administration of eggshell powder (T) which consists of 4 levels, namely: t0 = no treatment, t1 = 12.5 grams of polybag-1 eggshell powder, t2 = 25.0 grams of polybag-1 eggshell powder, t3 = 37.5 grams of polybag-1 eggshell powder.The results showed that administration of eggshell powder fertilizer had no significant effect on the time of first shoot (day), length of shoots 40 days, number of shoots 40 days and 80 days. But it has a very significant effect on the parameters of root length (cm). The results showed that the administration of ZPT Root-up concentrations had no significant effect on the time the first shoot appeared, but had a very significant effect on shoot length 60 days, 80 days, 80 shoots, root length (cm), and root weight (g). The results showed that the effect of eggshell powder interaction and ZPT Root-up had no significant effect on any plant parameters observed.